IMPLEMENTASI SISTIM INFORMASI MANAJEMEN RUMAH SAKIT DI RAWAT INAP RS PEKANBARU MEDICAL CENTER TAHUN 2024 - sri wahyuni; Hetty Ismainar; Adrian Mulya (Jurnal Keperawatan Abdurrab, 2025)
There is a demand for regulations stating that every health service must organize a hospital management information system and be able to manage and develop SIMRS such as electronic medical records. In its implementation, there are problems in inputting SIMRS. The purpose of this Residency Activity is to find out the problems in the implementation of SIMRS at Pekanbaru Medical Center Hospital, then find the root of the problem and make a plan of action from the problem. The method of Residency activities is qualitative with observation and in-depth interviews. The results of the residency show that the priority problem in SIMRS implementation is the absence of evaluation activities in SIMRS implementation. The researcher provides a plan of action recommendation for evaluating SIMRS implementation, for example by using satisfaction surveys, conducting internal electronic medical record audits, forming a SIMRS Implementation Special Assessment Team, and developing SIMRS so that evaluating SIMRS implementation becomes easier. Keywords: Evaluation, Implementation, SIMRS